Firefighters' Health Knowledge, Cardiovascular Disease Risk Factors, and Sociodemographic Characteristics as Predictors of Firefighters Attitudes Toward Health. Issue 11 (16th November 2022) - Ras, Jaron; Leach, Lloyd
Abstract : This paper adds new knowledge on firefighters' attitudes toward physical activity habits, diet, cardiovascular disease risk factors in firefighters. The study noted significant predictors of firefighters' attitudes toward healthier lifestyles, according to sociodemographic characteristics and cardiovascular disease risk status, which may prove beneficial in reducing cardiovascular risk in this population. Abstract : Objective: The aim of the study is to determine the predictors of firefighters' attitudes toward health based on firefighters' knowledge cardiovascular disease (CVD) risk factors and sociodemographic characteristics. Methods: The study used a web-based cross-sectional, descriptive, and correlational research design. Convenience sampling was used to recruit 110 firefighters, males, and females, aged 18 to 65 years. Results: Firefighters' health knowledge, age group 30 to 39 years, and having CVD risk factors present were significant predictors of firefighters' attitudes toward regular aerobic exercise ( P < 0.05). Firefighters' health knowledge was a significant predictor of firefighters liking exercise to look physically fit, and health knowledge and the age group 20 to 29 and 30 to 39 years were significant predictors of firefighters liking exercise to be fit for firefighting ( P < 0.05). Conclusions: Health knowledge, age group, years of experience, and having CVD risk factors present were significant predictors of firefighters' attitudes toward health.